OTHR-23. Development of a cerebrospinal fluid liquid biopsy platform in pediatric patients with central nervous system tumors. (3rd June 2022) - O'Halloran, Katrina; Ostrow, Dejerianne; Christodoulou, Eirini; Bootwalla, Moiz; Yellapantula, Venkata; Chapman, Nicholas; Chiarelli, Peter; Chu, Jason; Krieger, Mark; Gai, Xiaowu; Biegel, Jaclyn
Abstract: Pediatric central nervous system (CNS) tumors carry high morbidity and mortality. The advent of targeted agents is aiming to change that through individualized, less invasive, and real-time molecular profiling. We successfully developed a cerebrospinal fluid (CSF) liquid biopsy (LB) platform combining low-pass whole genome sequencing (WGS) and targeted mutation and gene fusion analysis of cell-free (cf) DNA. WGS libraries were constructed with the xGen Prism DNA Library Prep Kit using 5ng of input cfDNA and paired-end sequenced (Illumina NextSeq 500) for an average 0.5x coverage across the genome. Copy number (CN) profiles were analyzed using the ichorCNA R package and compared with CN abnormalities of the primary tumors detected with CytoScanHD or Oncoscan arrays. Selected cases were analyzed for mutations or gene fusions using a custom glioma hybrid capture-based panel (Twist Bioscience) sequenced to 500-1000x across targeted regions. Mutations identified in LBs were compared with primary tumor OncoKids NGS panel results. CSF LBs from 44 tumor cases and 15 non-tumor controls were analyzed. Sixteen primary tumors had copy number changes, 10 had cfDNA detected in the LB across various primary tumor diagnoses (AT/RT, diffuse midline glioma, ependymoma, high-grade glioma, medulloblastoma, pilocytic astrocytoma). Four primary tumors had sequence alterations from the custom panel, two with detectable cfDNA (diffuse midline glioma H3K27M variant allele frequency (VAF) 49% and low-grade glioma BRAFV600E VAF 1.7%). Three patients had TP53 variants detected, all ultimately germline. Controls were negative across WGS and hybrid gene capture. Tumor DNA is detectable by both WGS and hybrid gene capture. Various histologic subtypes are detectable including embryonal and glioneuronal. CSF seems more enriched for cfDNA in high grade versus low grade tumors. These data suggest that NGS-based LB assays may be used to monitor pediatric patients with a variety of CNS tumors, from diagnosis through treatment and recurrence.